Understanding rural people as participants in rural development. - Jali, Nazaruddin (1982)
Communities have suffered from projects designed for their well being. This happens either because the project has failed or new and unforseen phenomena have emerged. More often than not the root of problems may be traced to the insufficient understanding of the community or the environment. The Welstanschanung or the philosophy of life of the rural person; the process of change and related elements; and implications on participation are discussed.